PENYELESAIAN PERJANJIAN PEMBERIAN KREDIT DENGAN JAMINAN KEPEMILIKAN KENDARAAN BERMOTOR DI PERSEROAN TERBATAS BANK PERKREDITAN RAKYAT UNIVERSITAS GADJAH MADA YOGYAKARTA - Chaeroni, Ahmad; Mustafida, Latifa (Fortiori Law Journal, 2021)
This study aims to discuss and examine how the process of granting credit with guaranteed proof of motor vehicle ownership (BPKB) is carried out at the Limited Liability Company of the People's Credit Bank, Universitas Gadjah Mada (PT. BPR UGM) Yogyakarta. How is the implementation of the granting of the credit principle and what are the steps given in the event of bad credit or default. As is known, credit is one of the main services provided by financial institutions. In granting credit, one of the guarantees that can be given is BPKB which is included in the fiduciary guarantee category. From the granting of credit, we can review how it is implemented, the procedure for registration, whether the process is in accordance with the applicable legislation, what steps are being taken as a solution. Thus this research can serve to see the extent to which the implementation of fiduciary guarantees is effective in providing guarantees and protection for the bank. This research is empirical juridical type. Data collection was done by interviewing PT. BPR UGM Yogyakarta and explore data from primary materials obtained in the field. Secondary and tertiary data will be taken from books, laws and other regulations related to and supporting research. To get the results of the study, used descriptive analytical data analysis.The results of the study stated that the implementation of fiduciary guarantees with BPKB at PT. BPR UGM Yogyakarta has complied with the regulations regarding credit and fiduciary guarantees. The steps chosen by PT. BPR UGM Yogyakarta in the event of a default, including preventive measures such as direct warnings and deliberation and repressive efforts by confiscation and selling objects directly. The obstacles experienced can be categorized into 2 (two) namely internal constraints such as from the debtor himself and external constraints originating from the state economy or unstable business conditions.